2019
DOI: 10.1155/2019/8010614
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Ferroptosis in Acute Kidney Injury

Abstract: Acute kidney injury (AKI) is a heterogeneous group of critical disease conditions with high incidence and mortality. Vasoconstriction, oxidative stress, apoptosis, and inflammation are generally thought to be the main pathogenic mechanisms of AKI. Ferroptosis is a type of iron-dependent nonapoptotic cell death characterized by membrane lipid peroxide accumulation and polyunsaturated fatty acid consumption, and it plays essential roles in many diseases, including cancers and neurologic diseases. Recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 81 publications
4
116
0
Order By: Relevance
“…52 It was demonstrated that mitochondrial biogenesis also upregulates a broad spectrum F I G U R E 4 GC7 (N1-guanyl-1,7-diaminoheptane) treatment maintained antioxidative and mitochondrial protective pathways after kidney cold storage. Protein expression level of hypoxia-inducible factor 1-alpha (HIF1α) (A), ratio phosphorylated sirtuin (SIRT1)/SIRT1 (active SIRT-1) (B), SIRT3 (C), ratio phosphorylated Ser-616 dynamin-related protein-1 (DRP1)/DRP1 total (active DRP1) (D), mitofusin-2 (MFN2) (E), and ratio MFN2/ active DRP1 (F) detected by Western blot, and peroxisome proliferator-activated receptor-gamma coactivator-1-alpha (PGC1α) (H), nuclear factor (erythroid-derived 2)-like 2 (NRF2) (I), mitochondrial uncoupling protein (UCP2) (J) and UCP3 (K) mRNA levels at the end of cold storage (18h Ferroptosis is iron-dependent nonapoptotic cell death and is characterized by the accumulation of iron, ROS, and lipid peroxidation products 61,62 that acts in renal IRI. 63,64 Interestingly, NRF2 and HO-1 are identified regulators involved in regulating ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…52 It was demonstrated that mitochondrial biogenesis also upregulates a broad spectrum F I G U R E 4 GC7 (N1-guanyl-1,7-diaminoheptane) treatment maintained antioxidative and mitochondrial protective pathways after kidney cold storage. Protein expression level of hypoxia-inducible factor 1-alpha (HIF1α) (A), ratio phosphorylated sirtuin (SIRT1)/SIRT1 (active SIRT-1) (B), SIRT3 (C), ratio phosphorylated Ser-616 dynamin-related protein-1 (DRP1)/DRP1 total (active DRP1) (D), mitofusin-2 (MFN2) (E), and ratio MFN2/ active DRP1 (F) detected by Western blot, and peroxisome proliferator-activated receptor-gamma coactivator-1-alpha (PGC1α) (H), nuclear factor (erythroid-derived 2)-like 2 (NRF2) (I), mitochondrial uncoupling protein (UCP2) (J) and UCP3 (K) mRNA levels at the end of cold storage (18h Ferroptosis is iron-dependent nonapoptotic cell death and is characterized by the accumulation of iron, ROS, and lipid peroxidation products 61,62 that acts in renal IRI. 63,64 Interestingly, NRF2 and HO-1 are identified regulators involved in regulating ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A full understanding of the mechanisms hibernator cells use to sustain mitochondrial function and avoid ferroptosis during hypothermia may reveal the specific cellular protection mechanism, which may ultimately lead to the development of novel approaches to limit organ damage in, for example, transplantation, major surgery or cardiac arrest. Beyond these applications, this may possibly even apply to ferroptosis associated stress conditions comparable to hypothermia, such as stroke [38] and acute kidney injury [39].…”
Section: Cell Survival In Hibernator Cellsmentioning
confidence: 99%
“…In addition to the crosstalk between ferroptosis and other forms of cell death, the function and assay of ferroptosis related molecular and pathway need to be investigated. Some newly reported proteins such as PEBP1 [15], NCOA4 [16], and metallothionein-1G [17] are correlated with ferroptosis via iron metabolism and lipid peroxidation. In our GO and KEGG analysis, we found that the gene co-expressed with ACSL4 is enriched in the pathway of protein ubiquitination.…”
Section: Discussionmentioning
confidence: 98%
“…Further studies on ferroptosis are needed not only to clarify the molecular mechanism but also to provide an opportunity for designing new therapeutic interventions. For example, in the treatment of advanced hepatocellular carcinoma, sorafenib resistance has been shown to result from the metallothionein-1Ginduced inhibition of ferroptosis [17]. Lachaier et al compared the levels of ferroptosis induced by sorafenib with those induced by the reference compound erastin in a panel of human cell lines originating from various cancer tissues.…”
Section: Discussionmentioning
confidence: 99%